The Role of Destination Image in Building Loyalty of Halal Tourism Destinations: Satisfaction as Mediating Variable - Haryeni Haryeni; Yasri Yasri; Susi Evanita (AMAR (Andalas Management Review), 2022)
The purpose of this study was to determine the effect of cultural image, environmental image and socio-economic image on the satisfaction of tourists visiting the destination area in the city of Padang. The population in this study are tourists who visit tourist destinations in the city of Padang. Sampling in this study used a convenience sampling technique, namely any tourist who happened to meet the researcher, while each sampling was done randomly. The number of samples in this study were 150 respondents. The data analysis technique used in testing the hypothesis of this research is the use of the Partial Least Square (PLS) program. The results of the study found that cultural, environmental and socio-economic images had a significant effect on the satisfaction of tourists visiting tourist destinations in the city of Padang. The satisfaction has a significant effect on destination loyalty. Tourist satisfaction is influenced by cultural image, environmental image and socio-economic image by 63.5%. The higher the R-square value, the greater the ability of the independent variable to explain the dependent variable so that the structural equation is better.